Relationships of usage of facebook, awareness of facebook advertisements and contributing factors to consumers' purchasing behavior - Sasitharan, Githa Devi (2015)
Advertising has been Facebook‟s main revenue stream since its origin and it was believed the year 2010 as the year companies opened up significant new revenue streams, in which one of those was the virtual currency. However on the other hand,scholars as well as practitioners are debating on the actual effectiveness of Facebook advertising or marketing. Alternatively, there were scholars who had also claimed that is it still effective to invest in Facebook advertising, as it is cost effective as compared to other advertisements on the Internet. Therefore, this study aims to explore the debate above by further exploring effectiveness of Facebook advertisements in driving awareness as well as sales conversions. By using Hierarchy of effects theory framework as the fundamental of this study, this study will also further analyze on the factors that may have influence consumer‟s purchasing behavior through Facebook advertisements. Among the factors which were examined in this study are consumer‟s Facebook usage pattern, consumer‟s awareness towards Facebook advertisements which are categorized as consumer‟s awareness towards ads placed at home page, profile page, fan page and group page that they are member of. Besides, characteristics of Facebook advertisements were also another factor studied in this present study. The characteristics of Facebook advertisements were further categorized into 5 different factors, namely format of Facebook advertisements, color of Facebook advertisements, interactivity of Facebook advertisements, reliability of Facebook advertisements and relevancy of Facebook advertisements in affecting consumer‟s purchasing behavior. A quantitative research method was utilized by using a survey method. Systematic sampling method was used on 415 respondents, who were the working adults in Klang Valley. Data was collected using survey questionnaire. The gathered data were analyzed through both descriptive and inferential statistics. The findings of this study revealed that Facebook user‟s usage patterns do not have any relationship with consumer‟s purchasing behavior. This study also revealed that though consumers were aware of Facebook advertisements placed on their homepage, however they do not click on the ads or proceed with purchases through Facebook ads due to security and privacy reasons. Respondents were more willing to do online purchasing through Facebook advertisements if the retailer has safeguarded the security of the site. Besides, this study further concludes that by having group pages that are targeted besides ensuring the relevancy of the Facebook advertisement to the target audience, an advertiser could certainly increase consumer‟s affective behavior towards the advertised products and subsequently influence their purchasing decisions. There are two types of implications, which can be categorized from this study, which are academic implications and practical implications. As for the academic implications, this study most importantly provides exploratory evidence that may contribute towards online Advertising Avenue. Furthermore, the present study also contributes to the body of research in the area of, Hierarchy of Effects Theory that was used to build the fundamental structure of this entire study. As for the practical implications, the findings derived from the present study would potentially create impact in terms of marketing tactics that are being implemented by most of the advertisers in Malaysia.